Dextrose Equivalent (DE) Variation and Maltodextrin Concentration Effects in Yoghurt Powder Characteristics Using Foam-mat Drying - Eris, Fitria Riany; Pamela, Vega Yoesepa; Kusumasari, Septariawulan; Febriansah, Muhammad Rizal; Riyanto, Rifqi Ahmad (Department of Technology of Agricultural product (THP) Jambi University, 2023)
Lactic Acid Bacteria (LAB) in yoghurt is a probiotic bacteria which potentially improves intestinal health. Yoghurt has a high moisture content. Thus, storing it at low temperatures can maintain the stability of microbes in the yoghurt. Yoghurt stored in the refrigerator has a maximum shelf life of 10 days. Yoghurt powder is one of the alternative solutions to prolong the shelf life. This study used a randomized design of factorial groups with variations of dextrose equivalent (DE) values of 10-12 and 18-20, as well as variations of maltodextrin concentrations of 10, 15, and 20%. The study aimed to determine the DE value and maltodextrin concentration which can produce the best quality synbiotic yoghurt powder. The quality of this synbiotic yoghurt was assessed by the highest yield, lowest water content, highest solubility, highest water absorption, highest acidic titrated total, highest total of lactic acid bacteria, and highest organoleptic. The study obtained that the DE value of maltodextrin affected the total LAB. Meanwhile, the concentration of maltodextrin affected the yield, moisture content, solubility, acidic titrated total, and total of LAB. The interaction between the DE value and the concentration of maltodextrin did not affect all the parameters of this study.